(untitled) - Pugel, Thomas A. (New York, 2009)
This classic text has sold well for a half century because it covers all the conventional areas of international economics in an easy-to-understand manner. The 14th edition continues to provide the best blend of events and analysis, so that readers can build their abilities to understand global economic developments and to evaluate proposals for changes in economic policies. The book is informed by current events and by the latest in applied international research. It combines rigorous economic analysis with attention to the issues of economic policy that are alive and important today. This concise and readable text uses economic terminology when it enhances the analysis, but avoids jargon for jargon’s sake. Like earlier editions, it also places international economics events within a historical framework. The overall treatment continues to be intuitive rather than mathematical and is strongly oriented towards policy.
Keywords: International economic relations,Commercial policy,Foreign exchange; Kinh tế đối ngoại